2018
DOI: 10.1007/s00432-018-2673-x
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life chemotherapy is associated with poor survival and aggressive care in patients with small cell lung cancer

Abstract: EOL chemotherapy was correlated with shorter survival and more aggressive care in patients with SCLC. More research is needed to develop indications for terminating palliative chemotherapy, to help physicians and patients with their difficult choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…As death approaches for Chinese patients with terminal cancer, especially in the last 3 months of life, health resources increase substantially to extend life. 5 , 35 , 36 Our study found that patients had greater preference for comfort-oriented care with a high quality of life than in other studies. In 1 study, only 12.0% of patients with cancer in mainland China received palliative care with a high quality of life at EOL, 5 but we found that patients preferred care with a high quality of life.…”
Section: Discussionsupporting
confidence: 40%
“…As death approaches for Chinese patients with terminal cancer, especially in the last 3 months of life, health resources increase substantially to extend life. 5 , 35 , 36 Our study found that patients had greater preference for comfort-oriented care with a high quality of life than in other studies. In 1 study, only 12.0% of patients with cancer in mainland China received palliative care with a high quality of life at EOL, 5 but we found that patients preferred care with a high quality of life.…”
Section: Discussionsupporting
confidence: 40%
“…Another Chinese study found that the proportion of small cell cancer patients receiving chemotherapy in the last month of life was twice as high as in the last two months of life [31]. These data confirm that end-oflife cancer care and cancer deaths in China occurred overwhelmingly in hospital, with only 12% of mainland cancer patients receiving end-of-life palliative care [4].…”
Section: Discussionmentioning
confidence: 74%
“…O artigo A3 mostrou que pacientes com câncer avançado que receberam CP precocemente tiveram uma QV melhor do que os pacientes que tiveram acesso a estes cuidados tardiamente. Corroborando com este resultado, estudo (15) realizado na China com pacientes com câncer de pulmão pequenas células avançado, evidenciou que os sintomas com maiores intensidades foram dispneia, anorexia e perda de peso, os quais afetavam negativamente a QV, levando os autores a concluírem que o ideal para estes pacientes é acompanhamento precoce ou exclusivo em CP.…”
Section: -Domínios Que Interferem Na Qualidade De Viverunclassified